2016
DOI: 10.1159/000453192
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin Suppresses the Proliferation and the Mobility of Human Gastric Cancer Cells Through the Smad Signaling Pathway

Abstract: Background/Aims:Extensive studies have demonstrated that Bleomycin (BLM) is a glycopeptide antibiotic that has been used as an anticancer chemotherapeutic reagent. It can induce both single-and double-strand DNA damage, inhibit synthesis of DNA, suppress proliferation, and induce apoptosis in cancer cells. Smad signaling transducers are considered as important molecules in tumor development and progression, and may closely be related to the biological behaviors of some malignant carcinomas, including gastric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…It was reported that TGF-β not only participates in tumorigenesis and development of cancer [42, 43], but also regulates the immune response as a key immune inhibitory cytokine [44], resulting in immune escape within the tumor microenvironment. Treg cells were also shown to play a significant role in the suppression of local antitumor immune responses through TGF-β secretion [45].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that TGF-β not only participates in tumorigenesis and development of cancer [42, 43], but also regulates the immune response as a key immune inhibitory cytokine [44], resulting in immune escape within the tumor microenvironment. Treg cells were also shown to play a significant role in the suppression of local antitumor immune responses through TGF-β secretion [45].…”
Section: Discussionmentioning
confidence: 99%
“…The CCK-8 method (Dojindo, Kumamoto, Japan) was used to detect cell proliferation ability [24, 25]. Second-generation EPCs were cultured in a flat-bottomed 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…The Smad signaling pathway is a pivotal pathway in regulating a range of cellular functions in cancer cells, including proliferation, mobility, and apoptosis. 11 Central mediators of the Smad pathways are Smad2 and Smad3. They are phosphorylated and activated through the formation of the phosphorylation of Smad2 (ser465/467) and Smad3 (ser423/425).…”
Section: Introductionmentioning
confidence: 99%
“…They are phosphorylated and activated through the formation of the phosphorylation of Smad2 (ser465/467) and Smad3 (ser423/425). 11 P-Smad2 and P-Smad3 formed complexes with Smad4 that accumulate in the nucleus and regulate the progression of cancer cells. 11 This is the first report to show the influence of ING5 on the Smad signaling pathway in OS cells.…”
Section: Introductionmentioning
confidence: 99%